Pemetaan Daerah Rawan Longsor Berbasis Data Penginderaan Jauh di Kota Batu Jawa Timur - Armadyaputri, Aludra Nadia; Tanggahma, Yuan Zalfa; Darmawan, Yahya (Jagratara: Journal of Disaster Research, 2024)
Batu City is known to have a varied topography with high potential for landslides due to significant rainfall and certain geological conditions. Data observed in analyzing landslide prone areas include rainfall, slope, land cover, and soil type. The results of the analysis show that these factors play a significant role in determining the level of landslide vulnerability in the area. This study aims to analyze the level of landslide vulnerability in Batu City, East Java, using scoring and overlay methods. This method enables identification and mapping of landslide prone areas to provide recommendations for appropriate mitigation and management measures to reduce the risk of landslides. The resulting landslide vulnerability mapping provides useful information for authorities in planning effective mitigation strategies. The proposed mitigation action recommendations are expected to help reduce the impact of landslides and improve community preparedness in Batu City.